Optimal Oil-Owner Behavior in Piecewise Deterministic Models. (28th November 2013) - Seierstad, Atle
Abstract : Six simple piecewise deterministic oil production models from economics are discussed by using solution tools that are available in the theory of piecewise deterministic optimal control problems.